Antibiotic use in surgical units of selected hospitals in Ghana: a multi-centre point prevalence survey - Antoinette A. A. Bediako-Bowan; Enid Owusu; Appiah-Korang Labi; Noah Obeng-Nkrumah; Gifty Sunkwa-Mills; Stephanie Bjerrum; Japheth Awuletey Opintan; Cynthia Bannerman; Kåre Mølbak; Jørgen Anders Lindholm Kurtzhals; Mercy Jemima Newman (BMC, 2019)
Abstract Background Improper use of antibiotics leads to the emergence of resistant microorganisms as well as drug toxicity, increased healthcare costs, morbidity and mortality. Globally, an estimated 25-68% of hospitalized patients receive suboptimal antibiotic regimes. Information on the extent of this problem in Ghana is currently limited, particularly in surgical units. To strategize for interventions, we estimated the antibiotic use prevalence in surgical departments in a country-wide point prevalence survey (PPS) in Ghana. Methods Between October 2016 and December 2016, we conducted a cross-sectional multi-center country-wide PPS. This involved an audit of in-patients' records from all units/departments of ten systematically selected hospitals in Ghana. Data were collected with a standardized questionnaire, adopted from the European Centre for Disease Prevention and Control. In this report, we present data on antibiotic use from the surgical units. Results Of 2107 eligible patients included in the PPS, 540 patients were identified in surgical units, of which 70.7% (382/540) received antibiotic therapy. A total of 636 antibiotic prescriptions were issued to these surgical patients; 224 (58.6%) for treatment, including 50 for treatment of hospital-acquired infections, and 144 (37.7%) for prophylaxis (medical and surgical). Median duration of antibiotic therapy prior to the survey was 5 days (interquartile range (IQR): 3-8 days). Surgical prophylaxis was administered for longer than the recommended one day in 107 of 144 (88.4%) patients. The choice of antibiotics was largely similar for community- and hospital-acquired infections as well as for prophylaxis. Only 3.7% of patients had microbiological analysis done on clinical samples. Conclusion We found a high prevalence of antibiotic use, with the choice of antibiotics, in some cases, inconsistent with the country's treatment guidelines. Antibiotics were administered for long duration including antibiotics for prophylactic purposes and the majority was started without supporting microbiological analysis. Prescription practices that encourage rational use of antibiotics guided by microbiology and enforcement of antibiotic policy guidelines should be the target for future interventions.